PENERAPAN METODE PROMETHEE II PADA SISTEM LAYANAN DAN RUJUKAN TERPADU (SLRT) (STUDI KASUS : DINAS SOSIAL KABUPATEN DELI SERDANG) - Mesran, Mesran; Saputra, Imam; Ariska, Melinda (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2017)
Internet users find it difficult to compare and know the quality of services provided by Internet Service Providers (ISP), most Internet users choose an Internet Service Provider (ISP) based on the experience and advice of other users. This is not necessarily appropriate to the needs, because a valid decision must be considered and taken into account from the criteria available to obtain a decision. Decision support systems are designed to help decision making and are interpreted as a datadriven model system that has procedures in data processing and data processing results used to make a decision. Therefore, with the construction of decision support systems can help Internet users in making more efficient decisions. The method used in decision support systems is Elimintaion And Choice Translation Realty (ELECTRE). with the establishment of an Internet Service Provider (ISP) decision support system by applying the ELECTRE method that is expected to assist internet users in determining the Internet Service Provider (ISP) that suits their needs.